Outcome of pregnancy with acute appendicitis–a retrospective study - Bhardwaj, Suraj; Sharma, Shuchi; Bhardwaj, Vatika; Lal, Roshan (International Surgery Journal, 2021)
Acute appendicitis is the most common surgical non-gynaecological pathology during pregnancy. In this study, pregnant patients admitted with diagnosis of acute appendicitis in the last two years were evaluated retrospectively. Aim was to study the outcome of pregnancy with acute appendicitis. This was a retrospective study done on pregnant patients with acute appendicitis admitted between october 2017 and September 2019 in SLBS Government Medical College and Hospital, Mandi, HP. 7 pregnant patients were admitted for acute appendicitis. Patients were evaluated regarding age, gestational age, clinical and laboratory examinations, imaging studies, operative findings, mean hospital stay and outcome. In 4 out of 7 patients, acute appendicitis was confirmed and appendicectomy was performed. All of them were operated with open technique. There was no fetal or maternal morbidity or mortality in any patient. All patients delivered healthy babies during the postoperative course. Early surgical intervention is indicated if acute appendicitis is suspected. Pregnancy is not a reason to delay surgery.